2018
DOI: 10.1017/s0950268818001462
|View full text |Cite
|
Sign up to set email alerts
|

Multistate outbreak of Salmonella Paratyphi B variant L(+) tartrate(+) and Salmonella Weltevreden infections linked to imported frozen raw tuna: USA, March–July 2015

Abstract: Foodborne non-typhoidal salmonellosis causes approximately 1 million illnesses annually in the USA. In April 2015, we investigated a multistate outbreak of 65 Salmonella Paratyphi B variant L(+) tartrate(+) infections associated with frozen raw tuna imported from Indonesia, which was consumed raw in sushi. Forty-six (92%) of 50 case-patients interviewed ate sushi during the week before illness onset, and 44 (98%) of 45 who specified ate sushi containing raw tuna. Two outbreak strains were isolated from the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 11 publications
(12 reference statements)
1
14
0
Order By: Relevance
“…For S. Java, the CDC previously reported python-implicated outbreaks with isolates with 0 to 2 SNP differences; cases from other U.S. states that fell within the same cluster were not closely genetically related (up to 24 SNPs) (20). More recently, another S. Java outbreak from tuna reported clinical isolates with 0 to 4 SNP differences (21).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For S. Java, the CDC previously reported python-implicated outbreaks with isolates with 0 to 2 SNP differences; cases from other U.S. states that fell within the same cluster were not closely genetically related (up to 24 SNPs) (20). More recently, another S. Java outbreak from tuna reported clinical isolates with 0 to 4 SNP differences (21).…”
Section: Resultsmentioning
confidence: 99%
“…While a number of recent S. Java outbreaks have been linked to domestic exposure to aquatic pets or reptiles, including turtles (26), pythons (20), and aquariums (27), many outbreaks have been associated with contaminated food (28)(29)(30). Specifically, another multistate outbreak due to contaminated frozen raw fish was reported (21), which has far-reaching implications regarding the point of contamination; fish is often consumed raw as sushi (increasing the likelihood of infection) (21), and outbreaks may extend for months as frozen fish is thawed and consumed (15).…”
Section: Resultsmentioning
confidence: 99%
“…Fish and seafood consumption by the population is relatively high (21 kg per capita per annual) and cooking methods may vary (raw consumption or to avoid overcooking seafood), allowing the survival of bacteria. S. Weltevreden is increasingly associated with human infections and outbreaks in Southeast Asia where it appears to be an emerging foodborne pathogen [35][36][37]. It is known to be wide-spread in water-related environments, possibly due to its ability to persist and multiply in tropical aquatic environments [9,[38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a study identified the contamination of a cutting board by V. parahaemolyticus from raw squid as a cause of a gastroenteritis outbreak at a food bazaar in South Korea [ 65 ]. Further, there is a heightened health risk in consuming raw seafood, as evident from previous outbreaks associated with uncooked (or undercooked) fish, oysters, abalone or sea squirt [ 66 , 67 , 68 , 69 ].…”
Section: Pathogenic Bacteria In Foodmentioning
confidence: 99%